Pengembangan Ekonomi Kreatif Perempuan Disabilitas Griyo Melati Pasuruan Berbasis Modal Sosial - Iva Farkhanah (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the social capital of women with disabilities in the Griyo Melati Group. Social capital is a resource possessed by individuals or groups to create social networks or relationships within a community. The theory used in this study is Pierre Bourdieu’s theory of social capital, which demonstrates how women with disabilities have applied social capital to empower themselves within the Griyo Melati Group in Pasuruan. The objective of this study is to identify the forms of social capital utilized by Griyo Melati members particularly women with disabilities as a manifestation of creative economic development. This study uses a qualitative research method with a narrative approach. Informants were selected using purposive sampling. Data collection methods include observation, interviews, and documentation. Data analysis was conducted in three stages: data reduction, data presentation, and drawing conclusions/verification. The results of this study show that women with disabilities in the Griyo Melati Group utilize social capital namely economic capital, cultural capital, and social capital to foster the development of the creative economy. Economic capital is built up gradually and independently a portion of the proceeds from product sales is set aside and saved in the organization’s cash fund. The accumulated funds are then reinvested to acquire new physical assets. The Cultural Capital possessed by Griyo Melati consists of the ideas, innovations, and skills held by its members. Social Capital is utilized by partnering with several agencies of the Pasuruan City Government. Additionally, Griyo Melati actively participates in exhibitions, bazaars, and disability empowerment initiatives. These three forms of capital have enabled Griyo Melati to become a disability group that prioritizes creative economic development.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: Ekonomi Kreatif; Penyandang Disabilitas; Perempuan Disabilitas; Pemberdayaan; Pengembangan Ekonomi